An aeolian or a glaciolacustrine record? A case study from Mieļupīte, Middle Gauja Lowland, northeast Latvia - Nartišs, Māris; Kalińska-Nartiša, Edyta (Geologos, 2017)
In the Middle Gauja Lowland, northeast Latvia, dunes are distributed over a vast glaciolacustrine plain that formed during the retreat of the Fennoscandian ice sheet. Such a direct contact between aeolian and glaciolacustrine sediments can be used to infer depositional settings and decipher to what extent these sediments bear an aeolian component. Our proxies, although preliminary, reveal a limited range of variation in grain-size parameters, a significant presence of quartz grains with silica precipitation and matt-surface grains of various rounding degrees and massive structure combined with horizontal lamination. These are indicative of periglacial-aeolian depositional conditions in the foreland of the Linkuva ice-marginal zone. Sedimentary characteristics do not match a single luminescence date of 9.2±0.6 ka, which significantly postdates the minimum age of the Linkuva ice-marginal zone with 10Be ages between 15.4 and 12.0 ka. Whether deposition started directly after drainage of the Middle Gauja ice-dammed lake or if there is a gap of 2.8–6.2 ka is a matter of debate; only future studies at higher OSL resolution could resolve this.